The Effectiveness of Different Teaching Methods According to the Kolb Theory in Performance Accuracy of Some Basic Skills and Neuralgic Inhibition in Tennis - Aqeel Yahya Hashim Abdulaziz; Zainab Nadhim Shakir Al. Gburi (Journal of Global Pharma Technology, 2017)
In an attempt to use modern techniques in learning skills and believing that there is a need to re-examine the method used and provide the potential for the student to obtain information from them to ensure the process of education and to change the methods that are widespread based on memorization and conservation and literal application and replace them with modern methods to ensure the development of thinking and creativity capabilities of teachers and students And to benefit from modern information and techniques , And experimenting through the effectiveness of different teaching methods in accordance with the patterns of the theory of the circle Kolb in the performance of the accuracy of some basic skills in tennis. The aim of the research was to identify the classification of students according to the Kolb theory and the different teaching methods suitable for each classification, and to identify the best groups that were used according to Kolb's theory of performing some basic skills in tennis. The researchers hypothesized that the use of various teaching methods according to